TO LEAVE OR NOT TO LEAVE: THE CHU CI 楚辭 (VERSES OF CHU) AS RESPONSE TO THE SHI JING 詩經 (CLASSIC OF ODES). (September 2019) - Hunter, Michael
Abstract: Contra the consensus view of the Shi jing 詩經 (Classic of Odes) and Chu ci 楚辭 (Verses of Chu) as the products of two distinct literary cultures, one northern and one southern, this article argues on the basis of intertextual analysis that the Chu ci developed in direct response to the Shi jing . The foremost poem in the anthology, the "Li sao" 離騷 (Parting's Sorrow) emerges as a metadiscursive journey through various Shi jing archetypes, the goal of which is to authorize its hero to say farewell to his ruler and homeland—a possibility denied by Shi jing poetics. A final section explores the relationship between the oppositional poetics of the "Li sao" and the rest of the Chu ci . The article concludes with some reflections on the limitations of the north–south model for historians of early Chinese literature. 提要: 傳統觀點認為，《詩經》與《楚辭》分別是中國北方和南方兩種迥異文化的產物。與此相反，本文以文本互涉分析為基礎，主張《楚辭》發展於對《詩經》的直接回應。作為《楚辭》中最重要的篇目，〈離騷〉對《詩經》的諸多原型話題進行衍生，其目的是賦予主人公與君王和故國告別的權利。而在《詩經》的詩學體系中，這一選擇是不存在的。本文最後一部分探討了〈離騷〉與《楚辭》其他篇章相反的詩學關係。在結論部分，本文反思了早期中國文學史研究領域傳統中南北模型的局限性。